Consumer evaluation of retail hams from different production processes - Waldner, D.N.; Dikeman, Michael E.; Stroda, Sally L.; Campbell, R.E.; Kropf, Donald H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Consumers evaluated hams from the four minimum protein-fat-free categories labeled 1) ham (H), 2) ham with natural juices (HNJ), 3) ham-water added (HWA) and 4) ham and water product (HWP) for juiciness, flavor, and overall acceptability. Shear force and cooking loss data were also obtained. The HNJ product was rated higher for flavor and overall acceptability, whereas the Hand HWP were found to be the least desirable. The HWP was rated the most juicy; the H product was scored the least juicy. Peak shear force was lower for the HWP than for the other ham types; however, all hams were acceptably tender. The HWA and HWP had the least amount of cooking loss.
Keywords: Swine; Ham; Pork; Consumer; Evaluation